Behavior Contract Group Counseling Reduces Student Gadget Addiction - Nadra Araudha; Nefi Darmayanti (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Rapid digitalization in the 21st century has transformed human life, but excessive gadget use among adolescents has triggered health issues, reduced academic focus, and weakened social interaction. Specific Background: Observations at MTs Darul Ulum Budi Agung Medan revealed eighth-grade students displaying high levels of gadget addiction, highlighting an urgent need for effective counseling interventions. Knowledge Gap: Although group counseling is known to foster behavioral change, limited evidence exists on the specific efficacy of the Behavior Contract technique for reducing gadget addiction in Islamic junior high school settings. Aims: This study examined the effectiveness of group counseling using the Behavior Contract technique to reduce gadget addiction among students. Results: Using a quasi-experimental Non-Equivalent Control Group Design with 12 purposively sampled students, statistical analysis showed significant reductions in addiction in the experimental group (Wilcoxon Signed-Rank Test, p = 0.028; Mann-Whitney U Test, p = 0.004), unlike the control group. Novelty: This research introduces a structured Behavior Contract as a written agreement with reinforcement strategies, demonstrating measurable behavioral improvements in a religious school context. Implications: Findings suggest that integrating Behavior Contract-based group counseling into school guidance programs can effectively decrease gadget dependence, enhance discipline, and strengthen students’ learning focus and social interaction. Highlights: Proven effectiveness of Behavior Contract technique in reducing gadget addiction. Significant statistical results confirm measurable behavioral improvement. Practical integration into school counseling to enhance discipline and focus. Keywords: Behavior Contract, Gadget Addiction, Group Counseling, Quasi-Experimental, Student Intervention